Bioassay-guided identification of the antiproliferative compounds of cissus trifoliata and the transcriptomic effect of resveratrol in prostate cancer Pc3 cells - Méndez López, Luis Fernando; Caboni, Pierluigi; Arredondo Espinoza, Eder; Carrizales Castillo, Juan J. J.; Balderas Rentería, Isaías; Camacho Corona, María del Rayo (Multidisciplinary Digital Publishing Institute, 2021)
The bioassay-guided fractionation of a CHCl3 -MeOH extract from the stems of Cissus trifoliata identified an active fraction against PC3 prostate cancer cells. The treatment for 24 h showed an 80% reduction in cell viability (p ≤ 0.05) by a WST-1 assay at a concentration of 100 µg/mL. The HPLC-QTOF-MS analysis of the fraction showed the presence of coumaric and isoferulic acids, apigenin, kaempferol, chrysoeriol, naringenin, ursolic and betulinic acids, hexadecadienoic and octadecadienoic fatty acids, and the stilbene resveratrol. The exposure of PC3 cells to resveratrol (IC25 = 23 µg/mL) for 24 h induced significant changes in 847 genes (Z-score ≥ ±2). The functional classification tool of the DAVID v6.8 platform indicates that the underlying molecular mechanisms against the proliferation of PC3 cells were associated (p ≤ 0.05) with the process of differentiation and metabolism. These findings provide experimental evidence suggesting the potential of C. trifoliata as a promising natural source of anticancer compounds.